Antibiotic Treatment of Acinetobacter baumannii Superinfection in Patients With SARS-CoV-2 Infection Admitted to Intensive Care Unit: An Observational Retrospective Study - Casarotta, Erika; Bottari, Elisa; Vannicola, Sara; Giorgetti, Rachele; Domizi, Roberta; Carsetti, Andrea; Damiani, Elisa; Scorcella, Claudia; Gabbanelli, Vincenzo; Pantanetti, Simona; Marini, Benedetto; Donati, Abele; et al. (Frontiers in Medicine, 2022)
Introduction. In COVID-19 patients on mechanical ventilation, VAP from Acinetobacter Baumannii remains a crucial risk factor for death. Antibiotic resistance represents an important problem in treating this infection. This study aims to describe the evolution of the superinfection from PDR Acinetobacter Baumannii in patients with acute respiratory failure from SARS-CoV-2 infection admitted to ICU and compare the impact of two different antibiotic strategies on microbiological negativization. Methods. Single-center observational retrospective study, including patients, admitted to our ICU from March 2020 to May 2021, for acute respiratory failure from SARS-CoV-2 infection who developed PDR Acinetobacter Baumannii superinfection. Clinical data at ICU admission were collected, as well as the timing of isolation of Acinetobacter Baumannii, its resistance profile, the site of infection, and the antibiotic therapy. Results. Of the 32 patients enrolled, 10 patients (31.2 %) were treated with the combination of high-dose ampicillin/sulbactam, high-dose tigecycline, intravenous and inhaled colistin (Protocol), the other 22 (68.8%) were treated with the combination of two antibiotics (Control). Of the 10 patients in the Protocol group, 8 patients (80%) received also fosfomycin. All patients (100%) in the Protocol group had microbiological negativization, while in the Control group microbiological negativization was observed in 8 (36.4%) patients, p < 0.01. Conclusion. Our report shows microbiological negativization in all patients treated with the combination therapy of nebulized and intravenous colistin, high-dose tigecycline, and high-dose ampicillin/sulbactam. This combination of antibiotics seems to be a useful alternative when other treatments are not available or fail.